Enzymatically polymerised polyphenols prepared from various precursors potentiate antigen-specific immune responses in both mucosal and systemic compartments in mice - Tada, Rui (PLoS One, 2021)
Despite significant modern medicine progress, having an infectious disease is a major risk factor for humans. Mucosal vaccination is now widely considered as the most promising strategy to defeat infectious diseases; however, only live-attenuated and inactivated mucosal vaccines are used in the clinical field. To date, no subunit mucosal vaccine was approved mainly because of the lack of safe and effective methodologies to either activate or initiate host mucosal immune responses. We have recently elucidated that intranasal administration of enzymatically polymerised caffeic acid potentiates antigen-specific mucosal and systemic antibody responses in mice. However, our earlier study has not confirmed whether these effects are specific to the polymer synthesised from caffeic acid. Here, we show that enzymatically polymerised polyphenols (EPPs) from various phenolic compounds possess mucosal adjuvant activities when administered nasally with an antigen to mice. Potentiation of antigen-specific immune responses by all EPPs tested in this study showed no clear difference among the precursors used. We found that intranasal administration of ovalbumin as the antigen, in combination with all enzymatically polymerised polyphenols used in this study, induced ovalbumin-specific mucosal IgA in the nasal cavity, bronchoalveolar lavage fluid, vaginal fluids, and systemic IgG, especially IgG1, in sera. Our results demonstrate that the mucosal adjuvant activities of polyphenols are not limited to polymerised caffeic acid but are broadly observable across the studied polyphenols. These properties of polyphenols may be advantageous for the development of safe and effective nasal vaccine systems to prevent and/or treat various infectious diseases.